Tax Amnesty and the Evidentiary Standards of Ownership Transfer in Indonesian Corporate Tax Litigation - Kartiko, Nafis Dwi; Alex Oktobertus Pandapotan Gultom (Yayasan Cahaya Generasi Positif, 2025)
This study aims to analyze the role of tax amnesty in determining the standard of proof for asset ownership-transfer in corporate tax disputes in Indonesia, and analyze the implications of the tax amnesty policy on the implementation of state authority in the fiscal sector based on the principles of Indonesian constitutional law. Using a legal-normative method with a conceptual, statutory, and case study approach, it examines Tax Court Decision Number PUT-010465.12/2024/PP/M.XXA/2025. The results of the study show that tax amnesty not only functions as an administrative mechanism, but also as a declarative evidence tool that influences judicial assessments of share ownership transfers that are not fully reflected in formal documents. The court ruling confirms that although the Tax Amnesty Certificate does not have constitutive force, the document can be used to prove the economic substance of the transaction and the taxpayer's good faith in the asset ownership process. This study contributes to the expansion of understanding regarding the standard of proof in corporate tax litigation by positioning tax amnesty as a legal instrument that balances formal validity and material truth.